Multiphoton ionization of naphthalene clusters at 266 nm - Poveda, J.C.; Álvarez, I.; Cisneros, C. (Revista Mexicana de Física, 2011)
In this work we analyze the photoionization of Naphthalene clusters: dimmer, trimmer and tetramers when radiation of 266 nm from Nd:YAG laser at intensities up to 10^9 W · cm^ - 2 was used, in the range from 0.5 to 20.0 mJ per pulse. The clusters were formed by thermal desorption of a sample at 373 K and translational and vibrationally cooled in a jet by adiabatic expansion. At these experimental conditions the ionization processes were accomplished in the multiphoton regime by two photon absorption. A complete identification of fragment ions arising from the clusters was carried out, using a linear time of flight mass analyzer, ToF-MA. Evidence of proton and carbon atoms migration between molecular units in the clusters was observed, and the ions C_10H_8-H^ + and (C_10H_8)_2-H^ + were detected. The analysis of ion yield of clusters as a function of the energy per pulse showed that the dimmer stability is higher than trimmer and tetramer structures. The efficiency of clusters formation, and ionization processes were analyzed as a function of different carrier gases, CG: He, Ne, Ar, Kr and Xe. With He and Ne as CG, the ion yield decreases comparatively when Ar, Kr, Xe or not CG were used.